2005
DOI: 10.1200/jco.2005.17.624
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Genetic Profile of Intracranial Marginal Zone Lymphoma: A Primary Low-Grade CNS Lymphoma That Mimics Meningioma

Abstract: Our data suggest that intracranial MZBCL is an indolent primary CNS lymphoma that typically presents as a meningioma-like dural-based mass. Trisomy 3, but not MALT1 or IgH translocation, is a common genetic abnormality that may contribute to the pathogenesis of this CNS lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 44 publications
6
162
1
2
Order By: Relevance
“…28 The MZBCLs primary to the CNS, although very rare, are considered by some to be the most common low-grade PCNSL. 41 They differ from the other types of PCNSL discussed so far in that they typically are dura-based and mimic meningiomas. They are also notable for their favorable prognosis and higher incidence in women.…”
Section: Marginal Zone B-cell Lymphomas Of the Dura Matermentioning
confidence: 99%
See 2 more Smart Citations
“…28 The MZBCLs primary to the CNS, although very rare, are considered by some to be the most common low-grade PCNSL. 41 They differ from the other types of PCNSL discussed so far in that they typically are dura-based and mimic meningiomas. They are also notable for their favorable prognosis and higher incidence in women.…”
Section: Marginal Zone B-cell Lymphomas Of the Dura Matermentioning
confidence: 99%
“…41 The tumors involved mainly the dura mater and leptomeninges, with occasional instances of extension down Virchow-Robin spaces. Like MZBCLs elsewhere, the neoplastic lymphocytes were small to medium and had moderate amounts of cytoplasm and irregular nuclei, resembling follicular small-cleaved cells.…”
Section: Marginal Zone B-cell Lymphomas Of the Dura Matermentioning
confidence: 99%
See 1 more Smart Citation
“…Because they are morphologically indistinguishable from systemic DLBCLs, the World Health Organization classification of tumors of hematopoietic and lymphoid tissues does not recognize PCNSL as a separate entity [4]. The remaining cases of PCNSL are T-cell lymphomas (2%-5%) [5] or, in rare instances, low-grade B-cell lymphomas of the lymphoplasmocytic (Waldenström macroglobulinemia), follicular, or mucosa-associated lymphoid tissue type [6]. Little is known about the tumorigenesis of PCNSL.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…Since the initial description in 1997 by Kumar et al, 56 cases of primary meningeal MALT-NHL (PMML) have been reported so far [1][2][3][4][5], mostly under the form of case reports [2][3][4][5], but one large study [1]. Review of literature shows that PMML has somewhat common clinical characteristics and there are not well-established therapeutic guidelines.…”
Section: Primary Intracranial Meningeal Marginal Zone B Cell Lymphomamentioning
confidence: 99%